Quantification of urinary 18-hydroxycortisol using LC-MS/MS. (September 2013) - Jin, Shigeki; Wada, Norio; Takahashi, Yuji; Hui, Shu-Ping; Sakurai, Toshihiro; Fuda, Hirotoshi; Takeda, Seiji; Fujikawa, Masato; Yanagisawa, Katsuyuki; Ikegawa, Shigeo; Kurosawa, Takao; Chiba, Hitoshi
Background: Urinary 18-hydroxycortisol has been investigated as a marker of aldosterone-producing adenoma (APA). The aim of this study was to develop and validate a method for the measurement of 18-hydroxycortisol using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Methods: Urine was collected over a 24-hour period in patients with APA ( n  = 11), idiopathic hyperaldosteronism (IHA, n  = 9), and essential hypertension (EH, n  = 6). 18-Hydroxycortisol was extracted in solid-phase, and measured by LC-MS/MS based on selected reaction monitoring. Results: The method allowed quantification of 18-hydroxycortisol with a lower quantification limit of 0.26 nmol/L, intra- and inter-assay coefficients of variation of <3.4% and a range of analytical recovery of 98.0–103.7%. Urinary 18-hydroxycortisol excretion for APA, IHA and EH were determined as 725 (SD 451), 102 (SD 68) and 88 (SD 76) nmol/day, respectively. Conclusions: The proposed method met the basic analytical requirements and was considered to be useful in the screening and differential diagnosis of APA.